The Use of Kinesics as Nonverbal Communication in the Classroom at University of Muhammadiyah Bone - Gunawan Gunawan; Syarifuddin Dollah; Geminastiti Sakkir (PT ARRUS Intelektual Indonesia, 2024)
This study aimed to find out how the Use of Kinesics as Nonverbal Communication in the Classroom at the University of Muhammadiyah Bone. This research was a descriptive qualitative with 10 students as participants. They were taken by applying a purposive sampling technique. The research instruments are questionnaires and interviews. The result of this study shows that kinesics is an important element in non-verbal communication that can provide additional information and nuance to verbal messages. A deep understanding of body language can improve a person's ability to read and respond to communication more effectively.